i)
ax=ab+c
ax-ab=c
a(x-b)=c
a=c/(x-b)
ii)
3a+ab=6
a(3+b)=6
a=6/(3+b)
iii)
a(x-6)=3
a=3/(x-6)
i hope that this helps
2006-11-15 16:27:12
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
1, ax=ab+c
ax-ab=c
a(x-b)=c
a = c/(x+b)
2, 3a+ab=6
a(3+b)=6
a =6/(3+b)
3, a(x-6)=3
a =3/(x-6)
2006-11-15 08:41:53
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
a=c/x-b ,a=6/3+b ,a=3/x-6
2006-11-16 03:18:30
·
answer #3
·
answered by yomfun 1
·
0⤊
0⤋
1. ax-ab=c
a(x-b)=c
a=c/(x-b)
2. a(3+b)=6
a=6/(3+b)
3. a=3/(x-6)
2006-11-15 07:59:01
·
answer #4
·
answered by jade 3
·
0⤊
0⤋
ax-ab = c --> a(x-b) = c ---> a = c-(x-b)
3a+ab = 6 ---> a(3-b) =6 ---> a = 6/ (3-b)
the fird is easy a = 3/(x-6)
2006-11-15 07:51:29
·
answer #5
·
answered by maussy 7
·
0⤊
0⤋
a=c/(x-b)
a=6/(b+3)
a=3/(x-6)
Alternatively, buy a crown and declare yourself king of all maths. This also has the advantage of making x,b and c your subjects as well as "a".
2006-11-15 07:56:00
·
answer #6
·
answered by Nothing to say? 3
·
0⤊
0⤋
1)
x=b+c/a
x-b=c/a
a=c/x-c/b
2)
3a+ab = 6
3+b 6/a
2+6/b=a
3)
a=3/(x-6)
2006-11-15 07:46:41
·
answer #7
·
answered by phedro 4
·
0⤊
0⤋
1)
ax=ab+c
ax-ab=c
a(x-b)=c
a=c/(x-b)
2)
3a+ab=6
a(3+b)=6
a=6/(3+b)
3)
a(x-6)=3
a=3/(x-6)
2006-11-15 07:51:20
·
answer #8
·
answered by Amanda P 1
·
0⤊
0⤋
Learn transformation of formula
2006-11-15 08:36:22
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
ax=ab+c
ax-ab=c
a(x-b)=c
a=c/(x-b)
3a+ab=6
a(3+b)=6
a=6/(3+b)
a(x-6)=3
a=3/(x-6)
2006-11-16 11:32:53
·
answer #10
·
answered by Kemmy 6
·
0⤊
0⤋